Granulomatous rosacea: Like leukemid in a patient with acute myeloid leukemia - Škiljević Dušan; Čolović Milica; Bogatić Dragana; Popadić Svetlana; Medenica Ljiljana (Vojnosanitetski Pregled)
Introduction. Skin findings in leukemias may be divided into specific lesions (leukemia cutis) and non-specific lesions (leukemids) which may be found in up to 80% of all patients with leukemias. The leukemids vary clinically and they are usually a manifestation of bone marrow or immunologic impairment, but also Sweet syndrome, pyoderma gangrenosum, erythroderma, maculopapular exanthema, prurigo-like papules, generalized pigmentation, follicular mucinosis, generalized pruritus may be found during the course of leukemia. Case report. We report a 70-year-old male with a 3-month history of erythema, papules and pustules on the face, ears and neck and over a month history of refractory anemia, anorexia, weight loss, malaise, and fever. Physical examination revealed symmetric erythematous, violaceous papules, papulo-nodules and plaques with slate scale and sparse, small pustules on the face, earlobes and neck. Histopathologic findings of involved skin showed diffuse mixed inflammatory cell infiltrate with perifollicular accentuation and focal granulomatous inflammation in the papillary and upper reticular dermis. Extensive checkup revealed the presence of acute myeloid leukemia French- American-British (FAB) classification subtype M2, with signs of three-lineage dysplasia. The patient was treated by L6 protocol which led to complete remission, both in bone marrow and skin, but after seven months he had relapse of leukemia with the fatal outcome. Conclusion. This case indicates the importance of skin eruptions in the context of hematological malignancies.